Are National Physical Activity Guidelines Being Utilised in Local Government Policies? – A Survey on Awareness and Use of the Physical Activity Guidelines in Japan (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: In January 2024, Japan released revised physical activity guidelines for the first time in a decade: the Physical Activity Guide for Health Promotion 2023. Guidelines alone rarely induce population-level behavioural change. Thus, increased awareness and active utilisation among policymakers and professionals involved in physical activity promotion are crucial. The national health policy “Health Japan 21 (the Third Term)” was also updated, prompting local health plan revisions. This study aimed to assess the level of awareness of the new guidelines and the extent to which they were utilised in the development of local plans at the prefectural level.Methods: This study was conducted from February to April 2025. Surveys were sent to health departments in all 47 Japanese prefectures responsible for Health Japan 21 (the Third Term). The survey inquired whether, during the formulation of physical activity-related goals and strategies, they: (1) were aware of the 2023 guidelines; (2) referred to them during local plan development; (3) which specific sections they referenced; and (4) implemented measures, such as providing information, to promote awareness and utilisation among municipalities and related organisations. Responses were collected online, by mail, or email.Results: Out of the 47 prefectures, 38 responded (response rate: 80.9%). Of these, 30 (78.9%) reported being aware of the 2023 guidelines during plan development. Seventeen prefectures (44.7%) indicated that they referred to the guidelines. The most frequently referenced sections included the ‘Goals of Physical Activity in Health Japan 21 (the Third Term)’ (94.1%), and ‘Recommendations for Adults and Older Adults’ (82.4%). Additionally, 30 prefectures (78.9%) reported implementing initiatives to promote the guidelines among municipalities and related organisations.Conclusion: Most prefectural health departments in Japan were aware of the revised physical activity guidelines, and approximately 80% had implemented efforts to promote their use. Though improved by 15% from a 2016 survey, the proportion of prefectures referencing the guidelines remained below 50%. These findings highlight the need for further strategies to enhance guideline utilisation in policy development and dissemination, including future integration into sectors such as urban planning.Support/Funding Source: This study was supported by the Health and Labour Sciences Research Grant (JPMH22FA1004)